A revision of the turonian members of the ammonite subfamily collignoniceratinae from the United States western interior and gulf coast - Kennedy, W; Cobban, W; Landman, N (2001)
The Collignoniceratinae of the U.S. Western Interior first appear in the lower Turonian and range through the middle, and most of the upper, Turonian. For most of their range they are important biostratigraphic indicators. A review of their biostratigraphic distribution is provided and this is followed by a revision and/or discussion of the following taxa: Cibolaites molenaari Cobban and Hook, 1983, Collignoniceras woollgari woollgari (Mantell, 1822), C. woollgari regulare Haas, 1946, C. vermilionense (Meek and Hayden, 1860), C. jorgenseni n. sp., C. percarinatum (Hall and Meek, 1856), C. praecox (Haas, 1946), Collignonicerites collisniger n. gen., n. sp., Prionocyclus hyatti (Stanton, 1894), P. albinus (Fritsch, 1872), P. macombi Meek, 1876, P. bosquensis Kennedy, 1988, P. wyomingensis Meek, 1876, P. novimexicanus (Marcou, 1858), P. quadrants Cobban, 1953, P. germari (Reuss, 1845), P. pluricostatus n. sp., Prionocyclites mite Kennedy, 1988, and Reesidites minimus Hayasaka and Fukada, 1951. Collignoniceras woollgari, Prionocyclus hyatti, P. macombi, P. wyomingensis, P. novimexicanus, P. quadratus, and P. germari have been designated as zonal species in many publications, but aside from C. woollgari, P. hyatti, and P. wyomingensis, most of these species have not been well described in terms of their intraspecific variation. In many species, there is a gracile and a robust form, which may represent sexual dimorphs, but in most instances, the sample size of adult specimens is too small to prove this.